Oral vaccination of fish against vibriosis using spore-display technology - Gonçalves, Gabriela; Santos, Rafaela A.; Coutinho, Filipe; Pedrosa, Neide; Curado, Maria; Machado, Marina; Costas, Benjamin; Bonneville, Lourenço; Serrano, Mónica; Carvalho, António Paulo; Díaz-Rosales, Patricia; Oliva-Teles, Aires; et al. (Frontiers in Immunology, 2022)
Oral vaccines are highly demanded by the aquaculture sector, to allow mass delivery of antigens without using the expensive and labour-intensive injectable vaccines. These later require individual handling of fish, provoking stress-related mortalities. One possible strategy to create injection-free vaccine delivery vehicles is the use of bacterial spores, extremely resistant structures with wide biotechnological applications, including as probiotics, display systems, or adjuvants. Bacterial spores, in particular those of Bacillus subtilis, have been shown to behave as mucosal vaccine adjuvants in mice models. However, such technology has not been extensively explored against fish bacterial diseases. In this study, we used a laboratory strain of B. subtilis, for which a variety of genetic manipulation tools are available, to display at its spores surface either a Vibrio antigenic protein, OmpK, or the green fluorescence protein, GFP. When previously vaccinated by immersion with the OmpK- carrying spores, zebrafish survival upon a bacterial challenge with V. anguillarum and V. parahaemolyticus, increased up to 50 - 90% depending on the pathogen targeted. Further, we were able to detect anti-GFP-antibodies in the serum of European seabass juveniles fed diets containing the GFP-carrying spores and anti-V. anguillarum antibodies in the serum of European seabass juveniles fed the OmpK-carrying spores containing diet. More important, seabass survival was increased from 60 to 86% when previously orally vaccinated with in-feed OmpK- carrying spores. Our results indicate that B. subtilis spores can effectively be used as antigen-carriers for oral vaccine delivery in fish.